Seismic performance of a three-level health center with or without insulators - Arcaya Pancca, Pablo Cesar (2020)
The present work deals with the seismic performance of a building (health center) of three levels with or without insulators, which aims to know the methodology applied, analyze the results obtained and establish considerations that must be taken into account in the design of the insulators. The problem to be measured was the seismic performance in a three-level health center with or without insulators, with the types of insulators to be considered three types: highdamping insulators (HDR), lead-core insulators (LRB) and frictional pendulum (FPS). The methodology used was applying the Chilean regulation NCh2745-2003, the same that is an adaptation of the "international code for buildings" (IBC), for its acronym in English "which is based on an American standard for the design of insulators and through the modeling of the structure with a computational program such as SAP 2000. The results obtained were for an uninsulated structure, from the first to the last level it has values of 0.35, 0.34 and 0.29 sec. of fundamental period, for the case with high damping insulators the values of 2.98, 2.97, 2.56 of fundamental period were obtained, for insulators with lead core the values were 2.76, 2.75 and 2.38 and for insulators with frictional pendulum system the values were 1.24, 1.22 and 1.06 respectively. When comparing the seismic performance of a structure it is better with insulators, in comparison with a structure without insulators, being the insulators of high damping of better seismic performance